2013
DOI: 10.1093/aje/kws420
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Disturbances With Reduced Semen Quality: A Cross-sectional Study Among 953 Healthy Young Danish Men

Abstract: Several studies have found an association between sleep duration and morbidity and mortality, but no previous studies have examined the association between sleep disturbances and semen quality. We conducted a cross-sectional study among 953 young Danish men from the general population who were recruited in Copenhagen at the time of determination of fitness for military service between January 2008 and June 2011. All of the men delivered a semen sample, had a blood sample drawn, underwent a physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 41 publications
(50 reference statements)
5
63
3
1
Order By: Relevance
“…It has been reported that short and long sleep were associated with a higher prevalence of coronary heart disease, stroke, and diabetes, in addition to obesity and frequent mental distress, compared with optimal sleepers [15,16]. Lack of sleeping time may reduce sperm quality [7]. However, an extra hour of sleep in this study also showed lower sperm count and survival rate, suggesting the negative effect of sleeping too little or too much.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It has been reported that short and long sleep were associated with a higher prevalence of coronary heart disease, stroke, and diabetes, in addition to obesity and frequent mental distress, compared with optimal sleepers [15,16]. Lack of sleeping time may reduce sperm quality [7]. However, an extra hour of sleep in this study also showed lower sperm count and survival rate, suggesting the negative effect of sleeping too little or too much.…”
Section: Discussionmentioning
confidence: 61%
“…Sleep deprivation is now being recognized as an increasingly common condition inherent to modern society [4], so sleep loss not only is a social issue but also leads to a large number of human disorders, including male reproductive impairment [5]. It has been found that the frequency of sleep disturbances has increased in the industrialized world during the past few decades, and inadequate sleep can decrease semen quality [6,7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sleep restriction is associated with metabolic disorders such as obesity, insulin resistance, and diabetes . It was reported that sleep restriction resulted in a decrease in serum testosterone levels and reduced semen quality . Data suggest that sleep restriction during pregnancy results in biochemical, biometrical and behavioral alterations in offspring .…”
Section: Introductionmentioning
confidence: 99%
“…В пере-крестном исследовании 953 молодых мужчин зафик-сирована обратная U-образная зависимость между диссомнией и параметрами спермограммы [41]. Наиболее тесные отношения выявлены между степе-нью нарушений сна и общим количеством спермато-зоидов, их подвижностью, долей патологических форм и размером семенников.…”
unclassified